Editor's Foreword - Vadim Radaev (Journal of Economic Sociology, 2023)
Dear colleagues,Recently, on November 14, 2023, the results of the Third Grushin’s Book Award were announced. A festive ceremony praising the winners took place at the Moscow School of Social and Economic Sciences (Shaninka). We are proud to inform you that a major award went to the book What Do We Know About Freelancers? The Sociology of Free Employment (Moscow: HSE Publishing House, 2022) written by our colleagues doing economic sociology Denis Strebkov and Andrey Shevchuk (both from the LSES, HSE University). Our sincere congratulations to the win!